(untitled) (Scientific journal of the Fergana State University, 2023)
This article analyzes the differences between the wheat varieties of Uzbekistan and Belarus and how the soft and hard wheat varieties grown in both countries are of good quality and meet the quality requirements for consumption. The analysis used a number of indicators: density, chemical composition, acid content, volume in mm3, mass fraction of fat, protein fraction of fat, starch fraction of fat, all wheat varieties were analyzed and the varieties were adequate to the demand. ability to answer is checked. Four varieties of soft wheat grown in our country are "Bunyodkor", "Turkiston", "Ghazgon", "Khisorak" and two types of soft and one hard wheat "Laska", "Vasilisa" grown in Belarus. Varieties of "Kanveyer" were analyzed and their differences were determined.